Mulheres e agroecologia no Rio de Janeiro: construindo uma política feminista a partir das margens - Costa, Maria da Graça Silveira Gomes da (Brasil, 2019)
This study aims to understand the protagonism of women in the agroecological movement through their conceptions and practices. We take the feminist epistemology as theoreticalmethodological base, seeking to consider the various crossings that characterize these contexts, to look at the modes of subjectivation of activists within the movement of Agroecology, both in national sphere, and in the local sphere to following the women’s movement from Rio de Janeiro’s West Zone. As methodological tools, we use the analysis of documents of social movements and of the policies of promotion for Agroecology, interviews with activists and the participant observation of events, meetings and the daily lives of our speakers. The results indicate that: although the movements are building narratives based on the importance of the construction of feminisms and agroecology as social transformation projects that constitute each other, there still isn't a full recognition of the role and knowledge contributed by women; at the same time, international policies and programmes linked to The United Nations- U.N. mobilized an institutional discourse of empowerment that refers to neoliberal ideas considering the increase in production as a way to "equality" between genres. The results also show that in the scenario of crisis, militarization and precarious State in Rio de Janeiro, women are building a popular feminist politics from the margins, wich re-significating subalternized places to indicate other ways of politics, producing knowledge and occupy the cities. With this we see that agroecology is composed on a know-power that, if on one hand can be captured by speeches that try to undermine your potential insurgents, on the other hand, with the strategies that are being built especially from women, as an important vector of political subjectivation amidst urbans and rural social movements.
Keywords: Agricultura urbana; Epistemologia feminista; Agroecologia; Direito à cidade; Etnografia; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA